Self-efficacy and academic performance in higher education: a case study - Figueiredo, Elisa; Fonseca, Cecília; Paiva, Teresa (European Public & Social Innovation Review, 2024)
Introduction: There is a large body of research showing that self-efficacy is a crucial predictor of student achievement. Based on this framework, this study aims to investigate the correlation between students' general self-efficacy (GSE) and Social self-efficacy (SSE) and academic performance, as well as the relationship between GSE and SSE with age and gender. Methodology: Our approach was quantitative, descriptive, and cross-sectional. The target population was all students enrolled during the academic year 21/22 at a Portuguese higher education institution. Results: The results indicate that students with a high level of GSE perform better than those with lower GSE and the level of GSE depends on age and gender. Although, no correlation was identified for SSE and student performance. Discussion: From the results it was possible to corroborate the following study hypothesis: students with a high level of GSE perform better than those with lower GSE, the level of GSE and SSE depends on age and gender. Although the hypothesis set students with a high level of SSE perform better than those with lower SSE was not supported. Conclusions: This investigation could support strategies to promote self-efficacy in students with the aim of improving their academic performance.